U.S. agriculture and Third World economic development : critical interdependency - National Planning Association Food and Agriculture Committee (Washington, D.C. : National Planning Association, 1987)
Discusses the interdependency of U.S. agriculture and foreign agricultural/economic development which has raised contentious issues that concern farm and commodity groups; national and international development institutions etc.
Based on papers presented at a meeting sponsored by the NPA Food and Agricultural Committee and the Winrock International Institute for Agricultural Development, Oct. 1-3, 1986.
Includes bibliographical references.
occ 17/012019
Loans
Keywords: Agriculture - developing countries; Produce trade; Agriculture and state; Competition, International; International economic relations; United States; Developing countries